Comparison of Medical Treatment Cost Analysis Using Activity Based Costing and Double Distribution Method: A Scoping Review - Gunarti Gunarti; Chriswardani Suryawati; Septo Pawelas Arso (GLOBAL HEALTH SCIENCE GROUP, 2025)
Determining appropriate healthcare service tariffs is essential for hospital management to ensure financial sustainability, accessibility, and quality of care. Accurate tariff setting requires precise unit cost calculations. This study reviews and compares two widely used methods in healthcare cost analysis: Activity-Based Costing (ABC) and Double Distribution (DD). Using a scoping review guided by the PRISMA framework, literature was searched across Google Scholar, PubMed, Scopus, Web of Science, and the Cochrane Library with keywords “Activity-Based Costing,” “Clinical Pathway,” “Double Distribution,” “Financing,” and “Hospital,” limited to publications from 2019 to 2024. Eleven relevant studies were identified. The findings indicate that the DD method often underestimates costs, as it does not fully account for all healthcare activities, though it is easier to implement and widely used in Indonesia. In contrast, the ABC method provides a more detailed and accurate calculation by linking costs to actual activities, offering greater transparency for decision-making, though it requires comprehensive data and resources. Four studies applied ABC integrated with Clinical Pathways (CP), showing improved cost accuracy, quality control, and efficiency through standardized care processes. Overall, ABC, particularly when combined with CP, demonstrates stronger potential in supporting hospitals to set fairer tariffs and enhance service efficiency compared to the DD method.